Pemanfaatan Teknologi Informasi untuk Para Kader TPK Kec Simpang dalam Mencegah Stunting - salamudin salamudin; Dian Meilantika (Universitas Pahlawan Tuanku Tambusai, 2022)
This community service activity aims to increase the knowledge of family companion team cadres (TPK) at the district family planning extension centre in the utilization of information technology in preventing stunting. Due to chronic malnutrition, stunting babies grow shorter than the high standards of toddlers of their lifetime. With information technology, TPK cadres can find additional information about accelerating stunting prevention properly without being consumed by wrong issues or hoaxes in addition to the utilization of several smartphone applications available from android or iOS services that can be easily used. This activity was attended by TPK cadres from each village, also present as the chairman of Family Welfare Development (PKK) and the chairman of the Indonesian Midwife Association (IBI) of Simpang sub-district. This activity is carried out face-to-face with socialization methods by lectures using projector aids, demonstration or information technology utilization practices and the use of stunting prevention support applications. From this activity, the participants have been able to prevent stunting through information technology.